INFLUENCE OF ORGANIC FERTILIZER SAGO COMPOST ON ULTISOLS SOIL PHYSICAL PROPERTIES OF TELAGA KODOK SUB VILLAGE IN HITU VILLAGE OF CENTRAL MALUKU DISTRICT AND THE CORN (Zea Mays Ceratina) CORPS PRODUCTION - Silwanus M. Talakua; Elizabeth Kaya (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
This study aims to prove that the giving of organic fertilizer sago compost can improve soil physical properties and improve yields of maize crops on Ultisols. This research was conducted in Telaga Kodok Subvillage, Hitu Village Central of Maluku District in April 2016 until its completion. Soil analysis was conducted at Balai Penelitian Tanah Bogor. This research used Factorial Random Block Design which consist of one factor and repeated three times with compost dosage of sago compost is K0 (no compost), K1 (30 ton/ha), K2 (45 ton/ha), K3 (60 ton/ha ). Giving the ela sago compost can improve soil physical properties that is able to reduce the bulk density (0.73 g/cm3), particle density (1.78 g/cm3) and rapid drainage pores (7.69%) and able to improve/increase moisture content of field capacity (43.91%) and water available pore (17.00%). The ela sago compost as organic fertilizer can increase the yield of corn crop is 89,80 g/plant or 4,28 t/ha. The optimum dosage of ela sago compost as organic fertilizer found to improve soil physical properties and increase the yield of corn crop is 60 t/ha.